Lithium-Ion Mobility in Quaternary Boro−Germano−Phosphate Glasses - Moguš-Milanković, Andrea; Sklepić, Kristina; Mošner, Petr; Koudelka, Ladislav; Kalenda, Petr (My University, 2016)
Effect of the structural changes, electrical conductivity, and dielectric properties on the addition of a third glass-former, GeO2, to the borophosphate glasses, 40Li2O−10B2O3−(50−x)P2O5−xGeO2, x = 0−25 mol %, has been studied.
Mobilita lithných iontů ve sklech systému B2O3-GeO2-P2O5
Keywords: borophosphate glasses; Li2O; GeO2; structure; electrical conductivity; dielectric properties; borofosforečnanová skla; Li2O; GeO2; struktura; elektrická vodivost; dielektrické vlastnosti